Technical Note: Is bulk electron density assignment appropriate for MRI‐only based treatment planning for lung cancer?1. Issue 7 (12th May 2017) - Prior, Phil; Chen, Xinfeng; Gore, Elizabeth; Johnstone, Candice; Li, X. Allen
Abstract : Purpose: MRI‐based treatment planning in radiation therapy (RT) is prohibitive, in part, due to the lack of electron density (ED) information within the image. The dosimetric differences between MRI‐ and CT‐based planning for intensity modulated RT (IMRT) of lung cancer were investigated to assess the appropriateness of bulk ED assignment. Methods: Planning CTs acquired for six representative lung cancer patients were used to generate bulk ED IMRT plans. To avoid the effect of anatomic differences between CT and MRI, "simulated MRI‐based plans" were generated by forcing the relative ED (rED) to water on CT‐delineated structures using organ specific values from the ICRU Report 46 and using the mean rED value of the internal target volume (ITV) from the planning CT. The "simulated MRI‐based plans" were generated using a research planning system (Monaco v5.09.07a, Elekta, AB) and employing Monte Carlo dose calculation. The following dose‐volume‐parameters (DVPs) were collected from both the "simulated MRI‐based plans" and the original planning CT: D 95, the dose delivered to 95% of the ITV & planning target volume (PTV), D 5 and V 5, the volume of normal lung irradiated ≥5 Gy. The percent point difference and relative dose difference were used for comparison with the CT based plan for V 5 and D 95 respectively. A total of five plans per patient were generated; three with the ITV rED (rEDITV ) = 1.06, 1.0 and the mean value from the planning CT while the lung rED (rEDlung ) was fixed at the ICRU value of 0.26 and two with rEDlung = 0.1 and 0.5 while the rEDITV was fixed to the mean value from the planning CT. Results: Noticeable differences in the ITV and PTV DVPs were observed. Variations of the normal lung V 5 can be as large as 9.6%. In some instances, varying the rEDITV between rEDmean and 1.06 resulted in D 95 increases ranging from 3.9% to 6.3%. Bulk rED assignment on normal lung affected the DVPs of the ITV and PTV by 4.0–9.8% and 0.3–19.6% respectively. Dose volume histograms were presented for representative cases where the variations in the DVPs were found to be very large or very small. Conclusions: The commonly used bulk rED assignment in MRI‐only based planning may not be appropriate for lung cancer. A voxel based method, e.g., synthetic CT generated from MRI data, is likely required for dosimetrically accurate MR‐based planning for lung cancer.